2016
DOI: 10.1038/ncomms12708
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the interaction and disease mechanism of neurodegenerative disease-associated optineurin and TBK1 proteins

Abstract: Optineurin is an important autophagy receptor involved in several selective autophagy processes, during which its function is regulated by TBK1. Mutations of optineurin and TBK1 are both associated with neurodegenerative diseases. However, the mechanistic basis underlying the specific interaction between optineurin and TBK1 is still elusive. Here we determine the crystal structures of optineurin/TBK1 complex and the related NAP1/TBK1 complex, uncovering the detailed molecular mechanism governing the optineurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 49 publications
(107 reference statements)
6
110
0
Order By: Relevance
“…ALS/FTD‐associated mutations in the ubiquitin‐binding domain either reduce the normal function of optineurin by affecting its ability to interact with LC3 or act in a dominant‐negative manner to compromise autophagic activity (Wong & Holzbaur, ; Shen et al , ). Disease mutations in optineurin such as E696K also disrupt the formation of an optineurin/TBK1 complex (Li et al , ). Functionally, phosphorylation of optineurin by TBK1 promotes the binding of optineurin to its cargoes such as damaged mitochondria (Heo et al , ; Richter et al , ).…”
Section: Autophagymentioning
confidence: 99%
“…ALS/FTD‐associated mutations in the ubiquitin‐binding domain either reduce the normal function of optineurin by affecting its ability to interact with LC3 or act in a dominant‐negative manner to compromise autophagic activity (Wong & Holzbaur, ; Shen et al , ). Disease mutations in optineurin such as E696K also disrupt the formation of an optineurin/TBK1 complex (Li et al , ). Functionally, phosphorylation of optineurin by TBK1 promotes the binding of optineurin to its cargoes such as damaged mitochondria (Heo et al , ; Richter et al , ).…”
Section: Autophagymentioning
confidence: 99%
“…In contrast to autophagy receptor Optineurin, which may directly bind to TBK1 as demonstrated by our previous study (Li et al, 2016), NDP52 and TAX1BP1 rely on NAP1 and/or SINTBAD to associate with TBK1. Previous studies indicated that TBK1, together with NDP52, TAX1BP1 and Optineurin, was recruited to the ubiquitindecorated damaged mitochondria in the depolarization-dependent mitophagy as well as the invading pathogen in xenophagy, and cooperated with those autophagy receptors in selective autophagy (Heo et al, 2015;Lazarou et al, 2015;Richter et al, 2016;Thurston et al, 2016;Thurston et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…However, due to the lack of systemic characterization, the precise working mode of SKICH domain is still not well established. Interestingly, the Nterminal SKICH domains of NDP52 and TAX1BP1 are reported to interact with the adaptor protein NAP1 and SINTBAD (Thurston et al, 2009), both of which can further directly bind to the TBK1 kinase through their C-terminal TBK1-binding domains (TBD) (Li et al, 2016;Ryzhakov & Randow, 2007) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the expression of OPTN is tied to its propensity to oligomerise via dimer or tetramerisation or polyubiquitin chain binding leading to foci formation, sequestration of NFκ B or IRF3 signalling machinery and the inhibition of further signalling, possibly via autophagy. The OPTN E50K mutant displays a heightened propensity to form oligomers [47], and this property may explain the observed constitutive foci. Alternatively, the loss of ubiquitin binding seen with the OPTN E478G mutant might prevent foci formation by blocking oligomerisation through polyubiquitin chain binding.…”
Section: Discussionmentioning
confidence: 93%